AutoSpineAI: Lightweight Multimodal CAD Framework for Lumbar Spine MRI Assessments - Salem, Saied; Habib, Afnan; Raza, Mukhlis; Al-Huda, Zaid; Al-Maqtari, Omar; Ertugrul, Bilal; Al-Antari, Mugahed A. (Ieee, 2025)
Automated spine lumbar MRI analysis improves clinical workflow and diagnostic accuracy for lumbar spinal stenosis (LSS). In this paper, we introduce AutoSpineAI, a novel fully automated CAD framework for lumbar spine MRI analysis and structured medical report generation (sMRG) leveraging large language models (LLMs). The system processes 3D MRI DICOM volumes by extracting mid-sagittal slices for vertebrae and intervertebral discs (IVDs) segmentation and localizes corresponding axial slices using 3D cross-projection algorithm. For sagittal and axial slices segmentation, a novel lightweight efficient compact model (ECM) is proposed by integrating multi-attention mechanisms within a compact AI architecture to extract the quantitative spinal structural measurements (SSM): disc degeneration, vertebral anomalies, and other alignment irregularities. These structured measurements and assessments are integrated and merged in prompts for a novel hybrid agentic LLM-driven retrieval system that combines semantic information and knowledge graph-based reasoning to generate detailed level-wise diagnostic report: vertebrae and IVDs. AutoSpineAI achieves Dice scores of 97.58% and 94.01% for sagittal and axial segmentation, respectively, and generates a structured full report by Gemma3 LLM within 30 seconds per patient, achieving 83.51% Bert F1-score, 19.33% Meteor, and 15.31% Rouge1. AutoSpineAI seems to be a scalable and interpretable for clinical and practical solutions for MRI LSS.
2025 IEEE International Conference on Biomedical and Health Informatics-BHI-Annual -- OCT 26-29, 2025 -- Atlanta, GA
Keywords: Lumbar spinal stenosis (LSS); Computer-aided Diagnosis (CAD); Hybrid Agentic RAG; Large Language Model (LLM); Structured Medical Report Generation (sMRG)